2024
DOI: 10.21608/ejvs.2023.238918.1628
|View full text |Cite
|
Sign up to set email alerts
|

Some Semen Characteristics and Oxidant/Antioxidant Markers of Chilled Diluted Rabbit Semen in Tris-Based Extender Supplemented with Wheat Germ Extracts

walid EL-Nattat,
Islam El seadawy,
Mohamed Kotp
et al.

Abstract: HEAT germ(WG) was a rich source in antioxidants, and had antimicrobial effects also it proved to have anticold-shock effect in preservation of diluted semen. This study aimed to clarify how various types of wheat germ extracts (including oil, hydroethanolic, and water extracts) in combination with egg yolk contribute to the preservation of buck semen when subjected to the cooling procedure. WG was extracted with petroleum ether (for oil extract), hydroethanol extract and water extract. Chemical analysis of WG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The findings of present study showed that 4% Black cumin (Nigella sativa) seeds aqueous extract supplementation in tris egg yolk citrate extender could prolong the individual sperm motility (%) at pre-freeze (69.38±1.64) and post-thaw (46.56±1.35) stage. In accordance to this finding Awan et al (2018) [8] in buffalo; Miah et al (2018) [14] in ovine; Nasiri et al (2022) [12] in human; El-Battawy and Riad (2011) [15] in rabbit; Inanc et al (2021) [16] in ram; Al-Saaidi et al (2009) [17] , Mohammad et al (2009) [18] and Mansour et al (2013) [9] in rats, El-Nattat et al (2019) [19] in rabbit also reported higher sperm motility in lower concentration of Nigella sativa supplemented groups as compared to control group. The highest pre-freeze and post-thaw motility (%) found in T3 (4% Nigella sativa aqueous extract) group followed by T2 (3% Nigella sativa aqueous extract) group in present study, which was compliance with Awan et al (2018) [8] , who also found significantly (p<0.05) higher sperm motility in postcooling and post-thaw semen in 4% Nigella sativa extract group as compared to control group followed by 3% Nigella sativa extract supplemented group in buffalo semen.…”
Section: Results and Discussion Individual Sperm Motilitymentioning
confidence: 61%
See 1 more Smart Citation
“…The findings of present study showed that 4% Black cumin (Nigella sativa) seeds aqueous extract supplementation in tris egg yolk citrate extender could prolong the individual sperm motility (%) at pre-freeze (69.38±1.64) and post-thaw (46.56±1.35) stage. In accordance to this finding Awan et al (2018) [8] in buffalo; Miah et al (2018) [14] in ovine; Nasiri et al (2022) [12] in human; El-Battawy and Riad (2011) [15] in rabbit; Inanc et al (2021) [16] in ram; Al-Saaidi et al (2009) [17] , Mohammad et al (2009) [18] and Mansour et al (2013) [9] in rats, El-Nattat et al (2019) [19] in rabbit also reported higher sperm motility in lower concentration of Nigella sativa supplemented groups as compared to control group. The highest pre-freeze and post-thaw motility (%) found in T3 (4% Nigella sativa aqueous extract) group followed by T2 (3% Nigella sativa aqueous extract) group in present study, which was compliance with Awan et al (2018) [8] , who also found significantly (p<0.05) higher sperm motility in postcooling and post-thaw semen in 4% Nigella sativa extract group as compared to control group followed by 3% Nigella sativa extract supplemented group in buffalo semen.…”
Section: Results and Discussion Individual Sperm Motilitymentioning
confidence: 61%
“…They concluded that higher motility was due to positive effect of thymoquinone on aerobic respiration with oxidative phosphorylation enzyme and eliminating free radicals contributing higher motility. El-Battawy and Riad (2011) [15] found that at 200 µl/ml of Nigella sativa supplemented in tris-based extender could preserve sperm motility (%) significantly (p<0.05) higher as compared to control group at 2 nd day of incubation (5°C). They concluded that this positive effect on motility was due to antioxidant property and rich source of calcium, sodium potassium, iron that are essential for co-enzyme that protects sperm form cryo-damage.…”
Section: Results and Discussion Individual Sperm Motilitymentioning
confidence: 99%